THE EFFECTS OF THE DIVERSITY OF BANKING SERVICES ON BANK PERFORMANCE-A CASE OF THE IRAQI BANKING SYSTEM - J. Bakr, Dzoar; S. Mohamad, Idris (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the effect of diversification on the performance of various banks in Iraq. Previous studies suggest that banks that are less diverse in terms of services offered and clientele are monotonous and generate less revenue. Further, the performance of the bank is measured by its ability to meet its goals, increase its profit margin, and build a good capital portfolio. This research deployed qualitative and quantitative approaches to collect and analyze data from 19 participants in 7 companies within the Kurdish region of Iraq. The eligibility criteria for selecting the participants was that those who were fully aware of the functionality of the banks were selected. The findings showed that the diversity of services offered to clients influences the performance of the bank. In conclusion, banks that offer a variety of services to several investments are poised to perform in the banking industry. Employees also play a vital role in strategies such as the evaluation of clients and sectors with lower credit risk and higher returns.